Government by assassination - Byas, Hugh (George Allen& Unwin, 1943)
Text extracted from opening pages of book: GOVERNMENT BY ASSASSINATION B V HUGH BYAS ALFRED A KNOW NKW YORK PREFACE . he rise of Japan has been one of the major events of our age. Without Japan the present war would wear a very differ ent aspect. With Japan's entry into it the Pacific has become the theatre of sea-air warfare on a scale of speed and space never before known. The lines of communication are global; the battlefields are countries and oceans. Even before Japan doubled the task of the United Nations her achievement had been remarkable. In 1868 the news papers of the West reported the overthrow of the Tycoon of Japan and the restoration of a hitherto unsuspected Em peror